ANALISIS RASIO PROFITABILITAS SEBAGAI ALAT UNTUK MENILAI KINERJA KEUANGAN PADA PT. ACE HARDWARE INDONESIA Tbk (AHI) - Indri Astuti; Eka Safitri (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
This research aimed to examine the effect of Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM) on the financial performance of PT. Ace Hardware Indonesia Tbk (AHI) which were listed on Indonesia Stock Exchange. While, the data were secondary, in which taken from company’s financial statement 2014-2017. Moreover, the research was quantitative. In addition, the data analysis technique used descriptive statistics and inferential analysis with SPSS 25. From the data result, it concluded Return on Assets, Return on Equity, Net Profit Margin, and financial performance had good average score. Likewise, from the inferential analysis, it showed classical assumption test of all variables had fulfilled the assumption and there was no violence. As well as from the proper test model, it showed regression model was properly used. In brief, from the hypothesis result, it concluded Return on Assets and Return on Equity had significant effect on the financial performance. On the other hand, Net Profit Margin had insignificant effect on the financial performance.